China goes global: provenance, projection, performance and policy. Issue 1 (21st January 2019) - Buckley, Peter
Abstract : Purpose: The purpose of this paper is to examine the provenance, projection, performance and policy concerning Chinese outward foreign direct investment (COFDI) and speculate on the existence of "China's international strategy". Design/methodology/approach: This study includes a comprehensive review of COFDI. Findings: There is evidence of not only the successful coordination of COFDI, but also context, conflict and independent decision making (in Chinese firms) playing an essential role in the determination of the direction, control and outcomes of the outward FDI, respectively. Research limitations/implications: There is a great scope for further research on COFDI, as the lack of data prevents definitive conclusions, particularly on the outcomes and performance of the investments. Originality/value: The paper presents an original synoptic view of key elements in the globalisation of the world economy and in the projection of Chinese economic power.